Pengaruh konsentrasi larutan sukrosa dan waktu perendaman terhadap kesegaran bunga sedap malam potong (Polianthes tuberosa L.) - Eny Yuniati (Biocelebes, 2008)
Polianthes tuberose L. or known as tuberose is an example of the cut flowers, many of them sold in domestic as well as in worl-wide markets. In general, due to a post-harvested bad handling, its horticultural products were so bad and therefore, most of post-harvested flowers sold in a relatively cheap price or thrown away asa a waste. To overcome this problem, there had been established a research of how to keep the flowers in a fresh condition for a much longer time, and it was done by using a consentration of a di;utted sucrose to be given into a soaked fresh flowers of Polianthes tuberose L. an analytical result which used some diluted sucrose consentration and time of soakings to be recognized that, a consentration of 15% diluted sucrose in a two hourly time of soaking had a best result asa a fresh maker used by the cut flowers of tuberose. Key words : Post-harvest, Polianthes tuberosa, Soakings, Sucrose consentration.